Lymphoid follicles in chronic lung diseases. Issue 6 (8th January 2013) - Yadava, Koshika; Marsland, Benjamin J
Abstract : Lymphoid follicles (LFs) can be induced in the lung on infection or chronic inflammation; however, their relevance and contribution to protective immunity or pathogenesis is poorly understood. Recent advances from clinical studies and animal models have shed some light on the mechanisms that trigger and facilitate the development of LFs. As we grasp a better understanding of their development and their relevance to disease, the potential value in targeting pulmonary LFs with novel therapeutics will become evident.